2020
DOI: 10.1590/s1980-6574202000010198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of body image dissatisfaction and association with teasing behaviors and body weight control in adolescents

Abstract: The objective was to estimate the prevalence and the factors of behaviors of provocation and control of the weight associated with dissatisfaction with the body image among adolescents. Methods: Cross-sectional study with 580 adolescents (11 to 17 years old) from Criciúma, Brazil. The body image was evaluated by the silhouettes scale and the behaviors of provocation and weight control by questionnaires. A multinomial logistic regression was used (p ≤ 0.05). Results: Of the total number of adolescents, 48.6% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…20 Dissatisfaction due to thinness is recurrent mainly in male adolescents, due to the desire to have a stronger and more robust body. 4,21 However, in a study of this review, this type of dissatisfaction was more frequently reported by females. 4 In addition, children and adolescents in this systematic review also showed dissatisfaction due to excess weight (would like to reduce body weight), but these prevalences were not higher than those reported in relation to dissatisfaction due to thinness.…”
Section: Discussionmentioning
confidence: 51%
“…20 Dissatisfaction due to thinness is recurrent mainly in male adolescents, due to the desire to have a stronger and more robust body. 4,21 However, in a study of this review, this type of dissatisfaction was more frequently reported by females. 4 In addition, children and adolescents in this systematic review also showed dissatisfaction due to excess weight (would like to reduce body weight), but these prevalences were not higher than those reported in relation to dissatisfaction due to thinness.…”
Section: Discussionmentioning
confidence: 51%
“…Studies conducted in different part of the world have shown that, the prevalence of body image dissatisfaction in developed countries ranges from 35% to 81% in adolescent females and 16% to 55% in adolescent males [9,[17][18][19]. Despite data-based evidence from developed countries, little is known about the status of adolescent body image dissatisfaction and related factors in developing countries such as Ethiopia [23].…”
Section: Introductionmentioning
confidence: 99%